THE CONCEPT OF "PERSONALITY" IN PEDAGOGY AND SPECIFIC FEATURES OF PERSONALITY DEVELOPMENT - Zhakbarova Oyazimkhon Mutalipovna (American Journals, 2023)
This article describes the issues of personality development, the conditions that hinder personality development in the field of pedagogy, and the reasons that hinder their development. Also, the article presents the characteristics of the individual and the factors affecting their development and the existing conclusions.
Keywords: Personality, maturity, pedagogy, education, environment, factors, cause, essence, genetic characteristics, biological factors, teacher, skill.